C -reactive protein in assessment of severity acute pancreatitis - lslam, Kazi Mazharul; lslam, Md Aminul; Bhuiyan, Mashfique Ahmed; Muyaz, Azizur Rahman; Masum, Mohammad (Journal of Surgical Sciences, 2020)
Background: Acute pancreatitis (AP) is an acute inflammation of the pancreas and clinical evolution is frequently unpredictable. Numerous predictive markers have been studied to assess severity in AP, including clinical assessment, clinical-physiological scoring systems, imaging techniques, and biochemical markers in different body fluids. Objective: This study was done to see the association between level of CRP and severity of acute pancreatitis. Methods: 50 patients diagnosed as acute pancreatitis based on operational definition admitted in Dhaka Medical College Hospital was included in the study. Patients' admission date back from 1ST August, 2016 to 31december, 2015. Conservative management started from the date of admission as per standard conservative management protocol. Patients were monitored by RANSON scoring system and categorized as mild if RANSON score is <3 and categorized as severe if the score is ≥3. At the same time serum CRP level was measured on day 2, 3 and 7. Then the correlation between the severity of the disease and measures of CRP was established by unpaired t test and x2 test. Results: Over 6 months of study period 50 patients were treated for pancreatitis in different medical and surgical unit of Dhaka Medical College Hospital. Etiological analysis revealed mostly caused by biliary disease (40%) followed by idiopathic, alcoholic, post ERCP and post traumatic. Based on RANSON score about 34 patient developed mild acute pancreatitis and 16 patient developed severe acute pancreatitis. Then CRP value of this two groups was compared on day 2, 3, 7 by unpaired t test with P value<.001 in all 3 days. ROC curve was plotted to determine specificity and sensitivity with a cut off value of CRP 132mg/l. Sensitivity and specificity was 75% and 55.8% accordingly. Conclusion: In a patient with acute pancreatitis the use of RANSON scoring system is not always possible as many of the investigation are not easily available in our set up. In our study we have found that serum CRP level is significantly (cut off value 132) higher in patient with sever acute pancreatitis. This will allow high proportion of patients with mild disease to be managed in low-cost hospital beds. Acute pancreatitis is an important cause of hospital admission with acute abdomen. It is responsible for significant morbidity and also mortality in patients Journal of Surgical Sciences (2017) Vol. 21 (2): 80-84